Politeness Violation on Educational Utterance in Learning Interaction at Islamic Junior High School Bina Insani - Kusworo, Nanang; Rokhman, Fathur (Pascasarjana Universitas Negeri Semarang, 2019)
Language politeness in learning interaction has important role. Educational utterances violating politeness could influence to learning quality. Therefore, politeness violation of educational utterances could not be let in learning interaction. This research aims to analyze educational utterance politeness violation and its influential factors to educational utterances in learning interaction. The theoretical approach of this research is pragmatic while the methodological approach is analytic description qualitatively. The data was collected by participant observer through observing and extended techniques, such as recording and noting. Then, the data was analyzed qualitative descriptively. The findings showed the violations of politeness in educational utterances covered maxim of feeling, maxim of allowance, maxim of sincerity, maxim of sympathy, and maxim of agreement. Meanwhile, the influential factors of the violation were direct criticism, emotional motivation, and protective argument, subjecting the ilocutors, and intimidating ilocutors. This research expected to enrich research and knowledge dealing with learning interaction.